MOPHOLOGICAL CHARACTERIZATION OF POTATO (SOLANUM TUBEROSUM L) GERMPLASM FROM AZAD JAMMU AND KASHMIR - Sidra Nasar; Hajira Sabir; Saima Khan; Shamshad Aziz; Ansar Mehmood (Kashmir Journal of Science)
Current study was designed to investigate the diversity of agromorphological traits of five potato varieties from the state of Azar Jamal Kashmir. The investigative traits included qualitative as well as quantitative attributes including stem, leaf and tuber and yield. The data was Collected from 05 potato cultivation sites of AJK including Leepa, Shounthar, Taobut, Sudhan Gali and Kala Mula. They investigated varieties and showed significant variations in the qualitative traits including growth habit stem and leaf color as well as tuber and flesh colors. The results revealed that average values of Plant Height were 58.28 cm, Stem Thickness  5.66 mm, Leaf Length 15.66 cm, Leaf Width 10.44 cm, Leaflet Number 6.8, Flowering Time 61 days, Tuber Length 8.64 cm, Tuber Width 4.16 cm, Tuber thickness 5.78 cm, whereas average tuber yield per plant was 390.6 g. Results reveal that the investigative varieties exhibit significant morphological variations which reflect genetic diversity as well as adaptation of these varieties in diverse aggregate conditions of the region. The findings of current study provide baseline information about the potato germ plasm from the Azad Jammu and Kashmir region which holds significant implications for germplasm conservation and future breeding programs.